2019
DOI: 10.1007/978-3-030-24308-1_21
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Alumni Feedback System for Curriculum Improvement in Building Technology Courses

Abstract: In this fast-paced world, the needs of the world of work and the global market is changing at an unprecedented speed. Therefore, institutions of higher learning need to constantly adjust their programs to fit into these needs. The study aimed to develop an alumni feedback system for curriculum improvement in Building Technology courses. The study highlighted the benefits of an alumni feedback system compared to a manual questionnaire method or other methods of curriculum improvement. The web-based system was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, market research for educational institutions makes it possible to track and update the requirements of employers and the global market in educational activities and adjust them in time. A study by [6] showed the advantages of a feedback system for graduates compared to manual questionnaires or other methods of improving the curriculum, while [7] shows possible options for organising feedback from university applicants. High-quality feedback support is a modern web design trend [8].…”
Section: Feedback From External Contractorsmentioning
confidence: 99%
“…For example, market research for educational institutions makes it possible to track and update the requirements of employers and the global market in educational activities and adjust them in time. A study by [6] showed the advantages of a feedback system for graduates compared to manual questionnaires or other methods of improving the curriculum, while [7] shows possible options for organising feedback from university applicants. High-quality feedback support is a modern web design trend [8].…”
Section: Feedback From External Contractorsmentioning
confidence: 99%
“…The study developed a web-based system for plastics and paper waste management within a University community. In the system design, the study followed the patterns of the unified modeling language (UML) used in [ 18 , 19 ]. The UML used user case diagrams and system-block diagram.…”
Section: System Design and Implementationmentioning
confidence: 99%